A proposed framework using exploratory testing to improve software quality in SMEâs - Basri, S. (2019)
In the field of IT, the software industry recognizes the value of the small and medium software (SMEâs) enterprises in contributing valuable products and services to the economy. In SMEâs the quality of the software is increasingly become a concerned subject. The suitable use of testing standards was not written for the development organizations having less than 25 employees. Currently, most of the SMEâs do not follow any standards and do not adopt any well-structured testing methods. In this research paper, the challenges faced by the SMEâs towards software testing in order to produce quality products are being addressed. Various testing processes and other factors associated with software quality are analyzed and discussed in the literature review to identify the research gaps in the existing approach. In this research paper, a new framework has been proposed using Exploratory Testing that has not been used in the context of SMEâs which aims to improve software quality. Â© Springer Nature Switzerland AG 2019.